Bi-Mn mixed metal organic oxide: A novel 3d-6p mixed metal coordination network - Shi, Fa-Nian
A new terminology of metal organic oxide (MOO) was given a definition as a type of coordination polymers which possess the feature of inorganic connectivity between metals and the direct bonded atoms and show 1D, 2D or 3D inorganic sub-networks. One such compound was shown as an example. A 3d-6p (Mn-Bi. Named MOOMnBi) mixed metals coordination network has been synthesized via hydrothermal method. The new compound with the molecular formula of [MnBi2O(1,3,5-BTC)(2)](n). (1,3,5-BTC stands for benzene-1,3,5-tricarboxylate) was characterized via single crystal X-ray diffraction technique that revealed a very interesting 3-dimensional (3D) framework with Bi4O2(COO)(12) clusters which are further connected to Mn(COO)(6) fragments into a 2D MOO. The topology study indicates an unprecedented topological type with the net point group of (4(13).6(2)){4(13).6(8))(4(16).6(5))(4(18).6(10)){4(22).6(14)}(4(3)) corresponding to 3,6,7,7,8,9-c hexa-nodal net. MOOMnBi shows catalytic activity in the synthesis of (E)-alpha,beta-unsaturated ketones. (C) 2014 Elsevier Inc. All rights reserved.